Abnormal Return Saham LQ45: Sebelum dan Sesudah Demo DPR 2025 - Aprilia Nurhayati; Melania Pereira Lay; Risca Windy Nahtalia; Agus Satrya Wibowo; Ade Yuniati (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2026)
Purpose: The political case of the DPR demonstration on August 25, 2025, was used as a research gap with the aim of conducting empirical evidence whether there was a significant difference in abnormal returns before and after the event.Method: This research sampled 45 stocks in the LQ-45 Index using secondary data from daily closing stock prices and the Jakarta Composite Index (JCI). The parametric approach used was a paired simples statistical t-test, as the data were normally distributed.Results: An event study related to the August 25, 2025, House of Representatives (DPR) demonstration showed no significant abnormal returns before and after the demonstration. Investors considered this event irrelevant and material information for investment decision-making, and therefore did not trigger a systematic reaction in the Indonesian capital market.Implications: The findings of this study have practical implications for investors, urging them to avoid overreacting to specific political events and instead focus on company fundamentals. For regulators, these results demonstrate the maturity of the Indonesian capital market in responding to political turmoil.Novelty: This study addresses a previously undiscussed gap by developing a methodology that specifically analyzes the 2025 House of Representatives (DPR) demonstration, focusing exclusively on LQ-45 stocks. This study also develops a methodological approach using a combination of market-adjusted models and parametric tests that align with the characteristics of Indonesian capital market data.